Hacia una educación para la madurez - Ruiz Corbella, Marta (Revista Española de Pedagogía, 2018)
Nowadays, to educate as a means of achieving maturity has become the true goal of education and, I would willingly assert, it is the only way out of the crisis human beings are plunged into. It is a reliable option that will once again lead a man/woman towards finding himself/herself and learn to compromise with the realities which he/she is involved in, as well as to learn to accept the risks of life every one of us must experience in order to become the persons we should each be
Keywords: educación; madurez; Revista Española de Pedagogía